Problem-based Learning in Basic Physics — VIII - Mody, A.K.; Pradhan, H.C. (SCHOOL SCIENCE, 2025)
In this article, eighth in the series of articles, we present problems for a problem-based learning course based on dimensional analysis. We present the technique of dimensional analysis in the area of basic physics and what each problem tries to achieve with its solution.